Upper Limb Deep Vein Thrombosis in Patient with Hemophilia A and Heterozygosity for Prothrombin G20210A: A Case Report and Review of the Literature - Fares Darawshy; Yosef Kalish; Issam Hendi; Ayman Abu Rmelieh; Tawfik Khoury (Case Reports in Hematology)
Deep vein thrombosis (DVT) is a rare disease in patients with hemophilia A. We report a case of 22-year-old male with severe hemophilia A who presented to the emergency room with 5-day history of right arm pain that was attributed initially to bleeding event. In the absence of external signs of bleeding or hematoma and normal hemoglobin level, we suspected an underlying DVT. Doppler ultrasonography of the right upper limb revealed thrombosis of the subclavian vein and this was confirmed by CT venography. The d-dimer level was normal and investigations for prothrombotic state revealed heterozygosity for prothrombin G20210A mutation. Treatment with factor VIII and low molecular weight heparin led to successful resolution and marked improvement of his clinical condition.